Therapeutic Effect of Brucea Javanica Oil Emulsion in Mice with Irinotecan-Induced Delayed Diarrhea - Lai Z; Zhang Y; Hu X; Chen L; Huang W; Wang J; Chen B; Ren M; Yang B; Su Z; Chen J; Xie J; et al. (Drug Design, Development and Therapy)
Zixuan Lai,1,2 Yong Zhang,1 Xiaoxia Hu,1 Li Chen,1 Weimu Huang,1 Juan Wang,1 Baoyi Chen,3 Mihong Ren,1,2 Bowen Yang,1 Ziren Su,1,2 Jiannan Chen,1,2 Jianhui Xie,4,5 Zhengquan Lai,6 Youliang Xie1,2,5 1School of Pharmaceutical Sciences, Guangzhou University of Chinese Medicine, Guangzhou, 510006, People’s Republic of China; 2Dongguan Institute of Guangzhou University of Chinese Medicine, Dongguan, 523808, People’s Republic of China; 3Dongguan Hospital, Guangzhou University of Chinese Medicine, Dongguan, 523127, People’s Republic of China; 4State Key Laboratory of Traditional Chinese Medicine Syndrome, State Key Laboratory of Dampness Syndrome of Chinese Medicine, The Second Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, 510120, People’s Republic of China; 5Guangdong Provincial Key Laboratory of Clinical Research on Traditional Chinese Medicine Syndrome, Guangzhou, 510120, People’s Republic of China; 6Department of Pharmacy, Shenzhen University General Hospital/Shenzhen University Clinical Medical Academy, Shenzhen University, Shenzhen, 518055, People’s Republic of ChinaCorrespondence: Youliang Xie, School of Pharmaceutical Sciences, Guangzhou University of Chinese Medicine, Guangzhou, 510006, People’s Republic of China, Email xieyl@gzucm.edu.cn Zhengquan Lai, Department of Pharmacy, Shenzhen University General Hospital/Shenzhen University Clinical Medical Academy, Shenzhen University, Shenzhen, 518055, People’s Republic of China, Email cruise0303@163.comBackground: Chemotherapy-induced diarrhea (CID), particularly delayed diarrhea, often limits clinical use. Brucea javanica oil emulsion (BJOE), an adjuvant chemotherapy agent, has been shown to reduce irinotecan-related gastrointestinal side effects. However, its underlying molecular mechanism remains unclear. The cGAS-STING pathway, composed of the cytosolic DNA sensor cyclic GMP-AMP synthase (cGAS) and the adaptor protein stimulator of interferon genes (STING), plays an essential role in delayed diarrhea. This work aimed to investigate the therapeutic potential and underlying mechanism of BJOE on irinotecan-induced delayed diarrhea.Methods: Gas chromatography-mass spectrometry (GC-MS) was employed to explore the components of BJOE. Macro-observation, histology, PCR, immunohistochemistry, and Western blotting were performed to illuminate the potential mechanism of BJOE on irinotecan-induced delayed diarrhea mice model.Results: GC-MS analysis identified linoleic acid (20.67%) as BJOE’s main component. BJOE effectively mitigated irinotecan-induced delayed diarrhea in mice, as characterized by attenuation of weight loss, colon shortening, hematochezia, and histopathologic damage. It significantly inhibited the mRNA expression levels of inflammatory mediators TNF-α, IL-1β, IL-6, and iNOS, and upregulated barrier gene expression (ZO-1 and occludin). Furthermore, BJOE markedly enhanced mucin production, and increased PCNA protein expression. Concurrently, BJOE remarkably down-regulated the colonic mRNA levels of cGAS, STING, CXCL10, CCL5, and IFN-β. Activation of the cGAS-STING pathway with agonist DMXAA significantly reduced BJOE’s therapeutic, anti-inflammatory, and barrier-protective effects. Similarly, stimulating STING substantially reversed BJOE’s inhibition on cGAS-STING pathway.Conclusion: BJOE effectively mitigated inflammation and preserved intestinal barrier function, at least partially, via inhibiting cGAS-STING pathway in irinotecan-induced delayed diarrhea. Active components, long-term safety and pharmacokinetics studies were warranted to facilitate translational application. Keywords: brucea javanica oil emulsion, chemotherapy, irinotecan, delayed diarrhea, cGAS-STING pathway